Modern NMR spectroscopy in education - Rovnyak, David (Distributed by Oxford University Press, 2007)
This book will address the strong call for greater utilization of modern NMR in undergraduate education. There has yet been a book to note the numerous chemistry departments integrating NMR across their curricula. Researchers and educators are developing and implementing innovative experiments and pedagogies that are NMR-enabled. The proposed symposium series book will be the first publication to assemble and present these efforts, and will be a comprehensive resource for educators who wish to update their curricula with modern NMR experimentation. Significant progress has been made by educators in recent years to better incorporate modern NMR as an interdisciplinary tool for problem solving into first and second year courses such as general and organic chemistry; this book will report on and review many of these recent advances in first and second year chemistry. Significantly, the proposed book is explicitly designed as a comprehensive resource to educators